Review: Effect of drugs on human cough reflex sensitivity to inhaled capsaicin - Dicpinigaitis, Peter V (BioMed Central, 2012)
Capsaicin, the pungent extract of red peppers, has been used in clinical research for almost three decades. Capsaicin has gained favor as the provocative agent of choice to measure cough reflex sensitivity, as it induces cough in a safe, reproducible, and dose-dependent manner. One of the major uses of capsaicin cough challenge testing has been to evaluate the effect of a pharmacological intervention on the human cough reflex. The current review summarizes the published experience with capsaicin inhalation challenge in the evaluation of drug effects on cough reflex sensitivity. A notable contrast evident between studies demonstrating a drug effect (inhibition of cough reflex sensitivity) and those that do not, is the predominance of healthy volunteers as subjects in the latter. This observation suggests that subjects with pathological cough, rather than normal volunteers, comprise the optimal group in which to evaluate the effect of potential antitussive agents on human cough reflex sensitivity.